Hippocampal hyperactivity in a rat model of Alzheimer's disease. Issue 6 (5th March 2021) - Sosulina, Liudmila; Mittag, Manuel; Geis, Hans‐Rüdiger; Hoffmann, Kerstin; Klyubin, Igor; Qi, Yingjie; Steffen, Julia; Friedrichs, Detlef; Henneberg, Niklas; Fuhrmann, Falko; Justus, Daniel; Keppler, Kevin; et al.
Abstract: Neuronal network dysfunction is a hallmark of Alzheimer's disease (AD). However, the underlying pathomechanisms remain unknown. We analyzed the hippocampal micronetwork in transgenic McGill‐R‐Thy1‐APP rats (APPtg) at the beginning of extracellular amyloid beta (Aβ) deposition. We established two‐photon Ca 2+ ‐imaging in vivo in the hippocampus of rats and found hyperactivity of CA1 neurons. Patch‐clamp recordings in brain slices in vitro revealed increased neuronal input resistance and prolonged action potential width in CA1 pyramidal neurons. We did neither observe changes in synaptic inhibition, nor in excitation. Our data support the view that increased intrinsic excitability of CA1 neurons may precede inhibitory dysfunction at an early stage of Aβ‐deposition and disease progression. Abstract : Understanding the dynamics of pathological processes of Alzheimer's disease on the cellular and network level remains one of the challenging questions in basic and clinical research. Establishing hippocampal in vivo two‐photon Ca 2+ ‐imaging, we identified hyperactivity of CA1 neurons in transgenic McGill‐R‐Thy1‐APP rats during early Aβ‐plaque deposition. In brain slice patch‐clamp recordings, we find increased intrinsic excitability, but unchanged synaptic inhibition.